State of the art of lithium-ion battery material potentials: An analytical evaluations, issues and future research directions - Abu, Sayem M.; Hannan, M.A.; Hossain Lipu, M.S.; Mannan, M.; Ker, Pin Jern; Hossain, M.J.; Mahlia, T.M. Indra (Journal of cleaner production, 2023)
Recently, lithium-ion battery storage system has become increasingly popular due to its enormous potential and capacity in renewable energy integration and e-mobility applications leading to achieve global carbon neutrality by 2050. However, the performance of lithium-ion batteries has been affected due to the material degradation as well as varying environmental conditions. Thus, this paper presents analytical evaluation, aiming to investigate the advancement on the state-of-the-art of lithium-ion battery material potential that has been mapped from the hot papers. Accordingly, 73 hot papers (top 0.1% highly cited) have been found using the keyword search on lithium-ion batteries from the Web of Science database published in last 2 years between 2019 and 2021. These hot papers are evaluated using various key factors, including state-of-the-art of lithium-ion battery materials followed by analytical evaluation. The analytical assessment comprises numerous crucial aspects including keyword co-occurrence network analysis, distribution of articles over countries, journals, research types, and subject categories. Moreover, the review explores the concerns, issues and challenges to identify the existing research gaps. Finally, the review uncovers promising research opportunities and directions that will support the researchers towards energy efficiency, environmental sustainability of advanced lithium-ion battery management system. [Display omitted] •Lithium-ion battery material potential is analytically evaluated towards future research directions.•Hot paper earns a significant number of citations which is top 0.1 percent on the field.•The analytical evaluation is comprehensively done based on keyword co-occurrence network analysis.•Existing research gaps, issues and challenges on LIB materials are highlighted for future development.•This study will assist researchers and industries to develop an energy efficient advanced LIB.